Maintenance of anopheles darlingi, Root, 1926, in laboratory - Buralli, Geraldo Magela; Bergo, Eduardo Sterlino (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
The authors describe the installation and the initial efforts to maintain anopheles darlingi laboratory colonies in Araraquara - SP, as part of the Malaria Research Program - SUCEN. Based on other investigators' suggestions and on their own experience in the first six months of work, the authors present some modifications to the original methods of insect rearing, described by CORREA in the 70\s. The aim is to maintain insect colonies, using simple techniques and equipment. Information on larval and adult feeding, duration of larval instars, insect mortality and mating are provided.